Development of the high-speed boriding technology of alloy steel - Костик, Катерина Олександрівна (Eastern-European Journal of Enterprise Technologies, 2015)
The aim of the paper is to develop an easy-to-use and energy-efficient boriding nanotechnology of alloy steel parts, which is aimed at reducing the thermochemical treatment duration in obtaining high-quality boride layers, providing the necessary performance characteristics. The method of solving the problem was to find the optimum treatment temperature and time, and the influence of boriding process parameters on the hardened layer depth and hardness was studied for estimating the parameters characteristic of the diffusion layers. The research material was steel 30KhGSA. For paste boriding, the mixture based on nanodispersed boron-containing compounds was used. Heating was performed in a box furnace for 15 up to 120 minutes at temperatures ranging from 800 to 900°С. It was found that the increase in boriding temperature and time leads to the growth of borated layers and the transition zone. Paste boriding provides a surface hardness within 22-20 GPa with the decrease to 18-16 GPa along the layer to the transition zone. The obtained mathematical model and nomogram allow to determine the specific conditions of boriding (temperature and duration) based on a given layer depth of borides, which is of great practical importance. The resulting dependence of the experimental effective diffusion coefficient of boron for alloy steel confirmed the threefold acceleration of the boriding process. The practical significance of the work lies in the fact that the developed technology can be used on plants without having to install additional and update existing equipment. Thus, a new high-speed boriding method, allowing to carry out processing to produce high-quality diffusion layers was proposed.